Calculation of the vibrational excited states of malonaldehyde and their tunneling splittings with the multi-configuration time-dependent Hartree method - Schröder, Markus; Meyer, Hans-Dieter (The journal of chemical physics, 2014)
We report energies and tunneling splittings of vibrational excited states of malonaldehyde which have been obtained using full dimensional quantum mechanical calculations. To this end we employed the multi configuration time-dependent Hartree method. The results have been obtained using a recently published potential energy surface [Y. Wang, B. J. Braams, J. M. Bowman, S. Carter, and D. P. Tew, J. Chem. Phys. 128, 224314 (2008)] which has been brought into a suitable form by a modified version of the n-mode representation which was used with two different arrangements of coordinates. The relevant terms of the expansion have been identified with a Metropolis algorithm and a diffusion Monte-Carlo technique, respectively.